2014
DOI: 10.11646/phytotaxa.186.5.5
|View full text |Cite
|
Sign up to set email alerts
|

A new diploid butterwort species (Pinguicula, Lentibulariaceae) from Sardinia

Abstract: A new diploid species belonging to Pinguicula sect. Pinguicula is described from Sardinia, an island where no butterwort was previously reported from. The taxonomic relationship of P. sehuensis sp. nov. with other species is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Even if several researchers have studied this area in the past (e.g. Arrigoni, 1965;Loi and Lai, 2001;Loi et al, 2004), further endemic plant species were recently described or found, such as Pinguicula sehuensis and Senecio morisii (Bacchetta et al, 2014;Calvo and Aedo, 2015), until totalizing 99 endemic vascular plant species.…”
Section: Study Area and Target Speciesmentioning
confidence: 99%
“…Even if several researchers have studied this area in the past (e.g. Arrigoni, 1965;Loi and Lai, 2001;Loi et al, 2004), further endemic plant species were recently described or found, such as Pinguicula sehuensis and Senecio morisii (Bacchetta et al, 2014;Calvo and Aedo, 2015), until totalizing 99 endemic vascular plant species.…”
Section: Study Area and Target Speciesmentioning
confidence: 99%
“…Pinguicula sehunensis was recently described by Bacchetta et al . [1] as morphologically close to P . dertosensis , P .…”
Section: Discussionmentioning
confidence: 99%
“…longifolia subsp. reichenbachiana , endemic to few locations on the Maritime Alps in France and Italy, was already considered as a distinct species by several authors [1, 20, 21, 22], this is not the case for P . longifolia subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations